Brexit et souveraineté. Une mise en perspective juridique - Aurélien Antoine (Revue Française de Civilisation Britannique)
“Sovereignty” was undoubtedly the most widely manipulated word during the Brexit campaign, but this concept is very difficult to grasp. The legal point of view is a good place to start in order to explain its paradoxes and ambiguities. This paper aims, firstly, to explain the links between sovereignty and the exercise of powers by the State powers which had been, according to the Brexiters’ opinion, confiscated by the European Union. A second legal problem, a more specifically British one, is then analysed: the compatibility between the referendum and Parliamentary sovereignty. Finally, this paper confronts the legal conception of sovereignty presented in the first two points with a more concrete approach to sovereignty which takes into account the globalization of law and economic interdependence between nations.